Statistics and the quest for quality journalism a study in quantitative reporting - Martinisi, Alessandro ca. 20./21. Jh; Lugo-Ocando, Jairo 1968- (Anthem Press, 2020)
This book looks at how numbers and statistics have been used to underpin quality in news reporting. In doing so, the aim is to challenge some common assumptions about how journalists engage and use statistics in their quest for quality news. It seeks to improve our understanding about the usage of data and statistics as a primary means for the construction of social reality. This is a task, in our view, that is urgent in times of 'post-truth' politics and the rise of 'fake news'. In this sense, the quest to produce 'quality' news, which seems to require incorporating statistics and engaging with data, as laudable and straightforward as it sounds, is instead far more problematic and complex than what is often accounted for